IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI KOTA PEKANBARU TAHUN 2021 - Dwi Rahayu Ningsih; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The implementation of vaccination in Pekanbaru City in 2021 is considered not going well, because there are problems related to the implementation of the Covid-19 Vaccination implementation policy in Pekanbaru City. This study aims to determine and analyze the implementation of Pekanbaru City Government policies in the implementation of Covid-19 Vaccination and the inhibiting factors in implementing vaccination policies for the community in Pekanbaru City in 2021. This study uses policy implementation theory by looking at the elements, namely:1) tractability of the problem, 2) ability of policy decision to structure implementation 3) nonstatury variable affecting implementation. This research method uses descriptive qualitative methods. While the author's data sources use interview and documentation techniques. The location of this research is in Pekanbaru City. The results of this study indicate that the implementation of the vaccination policy in Pekanbaru City is based on the Presidential Regulation number 99 in 2020 and the Regulation of the Minister of Health of the Republic of Indonesia number 10 in 2021, which is related to the technical implementation and vaccination process. Meanwhile, the Pekanbaru City Government in implementing the vaccination policy can form a Mayor's Decree related to the task force for the acceleration of vaccination in Pekanbaru City. The implementation of community vaccination in Pekanbaru City involves all parties, including the Mayor of Pekanbaru, Regional Apparatuses, Regional Hospitals and Private Hospitals. The implementation of vaccination in Pekanbaru City achieve the 70% target by 2021. In addition, the impact of the vaccination policy in Pekanbaru City has an effect on the activities of the people of Pekanbaru City which are starting to improve. The inhibiting factors from the implementation of vaccination policies in Pekanbaru City are the limited dose of vaccine from the center, the lack of communication between the Pekanbaru City Government and the Riau Provincial Government regarding community vaccination data that is out of sync and the public understanding of Pekanbaru City is still negative about the impact of the vaccine. Keywords: Tractability problem, policy decision, variable affecting